Comprehensive Injury Prevention Strategies in Gymnastics: A Systematic Review of Biomechanical and Training-Related Risk Factors - Lubis, Hafiz Yazid; Corwin , Patsy; Kharatzadeh, Masoud; Kessler , Phoebe (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. To comprehensively analyze gymnastics injury prevention research, evaluate existing safety protocols, and identify best practices for reducing injury risks in middle school and competitive gymnastics programs through a systematic review of recent literature. Materials and methods. A systematic literature review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) methodology. The study examined peer-reviewed articles published between 2012 and 2024, focusing on human participants and injury prevention in gymnastics. A comprehensive electronic search was performed across multiple academic databases, utilizing search terms including "gymnastics injury prevention," "gymnastics safety," and "biomechanical risk factors." The research employed thematic analysis and qualitative comparative techniques to synthesize findings from 19 selected studies. Results. The review revealed alarming injury statistics, with 91.4% of gymnasts experiencing at least one injury per season and 480.7 musculoskeletal injuries per 100,000 person-years. Key findings highlighted the complex interplay of factors contributing to gymnastics injuries. These included specific biomechanical techniques affecting joint loading, correlation between training load and injury risk, impact of age and physical attributes on injury susceptibility, and significant variations in injury rates between national and non-national team gymnasts. Conclusions. The systematic review underscores the critical need for comprehensive, holistic approaches to gymnastics safety. Recommendations include developing standardized injury prevention protocols, implementing regular biomechanical assessments, enhancing coach education, and creating individualized training strategies that consider athletes' unique physiological characteristics and technical capabilities.